The effect of a mobile-based self-care program on tremor of people with multiple sclerosis - Abbas Safian; Shirmohammad Davoodvand; Morteza Sedehi; Shahram Tahmasebian; Nahid Jivad (Shahrekord University of Medical Sciences, 2022)
Background and aims: Multiple sclerosis (MS) is one of the most common progressive neurological diseases in young people. Tremor is a common and debilitating symptom in people with MS, significantly affecting their quality of life. This study aimed to evaluate the effect of a self-care program based on a mobile application on tremors in people with MS. Methods: This semi-experimental study was conducted on 72 patients with MS in Chaharmahal and Bakhtiari province in 2019. Samples were selected by convenience sampling and randomly assigned to intervention and control groups (36 people in each group). For the intervention group, a self-care program in the form of a mobile application was installed on their mobile phones and, for two months, used by patients. The use of the program was measured using self-report checklists and telephone tracking. The control group receives routine intervention only. Data were collected before and two months after the intervention using the Fahn-Tolosa-Marin Tremor Rating Scale and analyzed using SPSS software version 21 and descriptive and inferential statistics (chi-square, independent t test, and paired t test). Results: There was no statistically significant difference between the two groups in the mean tremor score before the intervention (P=0.768). However, after the intervention, this difference was significant (P=0.022). Conclusion: According to the findings, teaching a self-care program through a mobile application effectively improves the tremor of patients with MS and can be considered an effective intervention method.